A Local Wisdom Based Islamic Character Education Model for Developing Religious Moderation among Students at MA Diniyyah Al-Azhar Bungo - Nailis Sa'adah; Sugeng Kurniawan; Joni Juli Yandra; Wiwin Narti; Noviriani Noviriani (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2023)
This study aims to formulate and analyze a local wisdom-based Islamic character education model for fostering moderate attitudes among students at MA Diniyyah Al-Azhar Bungo, Jambi. Employing a qualitative approach with a case study design, data were collected over a six-month period through in-depth interviews, participant observation, and document analysis. The participants included the madrasah principal, Islamic Religious Education (IRE) teachers, students, and local customary leaders. Data were analyzed using Braun and Clarke’s thematic analysis technique, supported by source and method triangulation to ensure trustworthiness. The findings reveal that the integration of Jambi Malay local wisdom values—such as adat bersendi syarak, syarak bersendi kitabullah (custom founded upon Islamic law, and Islamic law founded upon the Qur’an), deliberative traditions (musyawarah), and the spirit of communal solidarity (salingka nagari)—into the hidden curriculum, contextual learning practices, and character habituation programs successfully strengthened four pillars of religious moderation: tawassuth (moderation), tasamuh (tolerance), i‘tidal (justice and balance), and muwatanah (citizenship). The resulting model consists of five strategic components: (1) identifying local values aligned with Islamic principles; (2) integrating these values into lesson plans and student profile strengthening projects; (3) implementing community-based character habituation programs; (4) positioning teachers as uswatun hasanah (role models); and (5) conducting multidimensional authentic assessments. These findings contribute to the development of a contextual Islamic Religious Education pedagogy that is aligned with the national agenda of religious moderation and adaptable to madrasahs in culturally diverse settings. Future studies are recommended to test the model quantitatively and longitudinally to validate its long-term impact on students’ religious attitudes.